Effect of air flowrate on the dynamic respiration activity of the raw organic fraction of municipal solid wastes. (January 2017) - Evangelou, Alexandros; Chintzios, Vassilios; Komilis, Dimitrios; Sánchez, Antoni
Highlights: Dynamic reactors were used to study the effect of UAF on the raw fraction of MSW. UAF correlates positively with OUR and CO2 consumption rate and cumulative indices. A statistically significant correlation was found among O2 and CO2 dynamic indices. The effect of UAF depends on the biodegradability of each organic substrate. DRI24 above/below 1500/520 mg O2 kg −1 VS h −1 indicate fresh/stable MSW material. Abstract: Scope of this work was to study the effect of the aeration rate on the respiration activity of the fresh organic fraction of MSW and to compare the resulting dynamic respiration indices with those of MSW derived compost. Thus, a categorization of the dynamic respiration activity of MSW throughout a composting facility is provided. A simulated organic fraction of MSW was used as a substrate and four experimental runs were performed to achieve unit airflow rates (UAF) from around 6 to 30 L air kg −1  VS h −1 . Six dynamic respiration activity indices were calculated and compared to the corresponding indices of stable MSW compost from a previous work. Findings indicate that the increase of the UAF results in a corresponding increase of the dynamic stability indices. Dynamic respiration activity indices above 1500 and below 520 mg O2  kg −1  VS h −1 indicate fresh and very stable MSW materials, respectively.